PERAN PETUGAS PENGAMANAN PINTU UTAMA (P2U) DALAM PEMERIKSAAN DAN PENGGELEDAHAN DI LEMBAGA PEMASYARAKATAN KELAS III BANDANAIRA - Niels Sohilat; Ali Maskur (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The research focuses on the optimization of the inspection and search of goods by the main door security (P2U) officers of the Bandanaira Marketing Institute of Class III. The process of search and inspection is carried out at the main gate by the P2U task unit against officers, people and goods that entered the door to maintain security and order in Lapas. Qualitative methods with observational approaches and field research with presentation of analytical descriptive data. The purpose of this study is to find out the optimization of the performance of P2U satgas inining order and security in Class III Lapas of Bandanaira by inspecting and tracking officers, visitors and goods. The author's conclusion is that Bandanaira's Class III Marketing Institution has not achieved maximum security and order in the area due to the lack of staff, professionalism and modern technology equipment such as X-ray. Secondly, the officers still feel weary in carrying out inspections of officers and officers in lapas.